Design and Implementation of Online Examination System for a Higher Educational Institution - Nyamupanemunda, Larry; Deshinta, Arrova Dewi (INTI International University, 2022)
When Covid19 was declared a world pandemic, online learning was to replace all the physical classes and examinations. The main concern would be managing question papers online and plagiarism opportunities that may occur during the examination. This paper highlights the developing an Online Examination System (OES) in the form of a web-based application that enables lecturers to manage their exam papers, assign them to their students, utilize auto-grading objective questions and provide feedback for subjective questions. The OES is accessible by mobile phone users whereby both lecturers and students are equipped with their dashboards to manage their needs. The OES framework focuses on a single university due to the closure of the campus and social distancing measurement to perform data collection. This paper includes the impact on the transition of physical to online examination, problem identification with solutions, and to what extent the OES can assist lecturers to conduct a smooth online examination. The OES was developed using PHP with MySQL, HTML, CSS, Bootstrap, JavaScript, and AJAX. The usability and user acceptance testing was conducted. The results show that most respondents agreed there is a need to have a system such as OES with future enhancements on the proctoring technology to prevent plagiarism. The outcome of usability testing was satisfactory and most respondents suggested including more enhanced features in the next development.